Serial step sections at narrow intervals with immunohistochemistry are required for accurate histological assessment of sentinel lymph node biopsy in oral squamous cell carcinoma. Issue 10 (15th June 2021) - King, Claire; Elsherif, Nusaybah; Kirwan, Ruaidhrí; Schilling, Clare; Hall, Gillian; Morgan, Peter; Collins, Lisette; Sandison, Ann; Odell, Edward; Thavaraj, Selvam
Abstract: Background: Sentinel lymph node (SLN) biopsy is an accurate staging modality in early oral squamous cell carcinoma (OSCC), but its accuracy relies on labor‐intensive histopathology protocols. We sought to determine whether serial step sections with immunohistochemistry (SSSIHC) at narrow intervals of the entire SLN are required to accurately exclude metastasis. Methods: Consecutive SLN biopsies over a 13‐year period were retrospectively evaluated. If the index section was negative for carcinoma, the entire SLN was subjected to SSSIHC at 150 μm intervals. The first section level and total number of section levels to contain carcinoma were recorded. Results: One hundred and eighteen SLN+ from 90 patients were included. SSSIHC upstaged the nodal status in 19.5% of patients. Metastasis was identified in 16.7% and 10.2% beyond section levels 4 and 6, respectively. Among SLNs requiring SSSIHC, 47.5% contained carcinoma in a single section level. Conclusion: SSSIHC of the entire SLN at 150 μm intervals are required to identify occult metastasis in OSCC.